Current practices of Islamic credit cards in Malaysia - Uddin, Mohi; Hossin, M.M. Ismail; Islam, Mohd Aminul (Scholars Middle East Publishers, 2017)
The practice of Islamic credit cards today is still controversial among Muslim scholars particularly concerning to its contracts and as well as its efficiency to attain Maslahah. The Islamic credit card is very important and some studies have done on it. Conversely, studying about the contrast of the various product of Islamic credit cards practiced in Malaysia, although in the recent year is still limited. Consequently, this paper would like to undertake this concern by comparing the various products of Islamic Credit Cards in Malaysia. Islamic credit card known as Credit Card-i is such of the alternate banking products instigated through Bank Negara Malaysia (BNM), also Islamic financial institutions in Malaysia to exchange the conventional credit card. This article aims on evaluating the bay‟ al-„Inah, Tawarruq as well as Ujrah development while practiced over Bank Negara Malaysia (BNM) as well as Islamic Financial Institutions in Malaysia with Shariah compliance perceptions. The method used is explanative along with positive absorbed criticism which aims next to well the offered structure.